Knowledge construal in the media. An analysis of the complex linguistic activity of criticism as a method of accessing knowledge in media discourses - Hanus, Anna (Papers in Linguistics, 2020)
As assumed in discourse analysis, certain politically or socially important discursive events trigger discursive actions in the media. Acting interest groups locate themselves with their knowledge in relation to a specific political or social event and try to assert their interests and positions in the discourse by distributing particular knowledge about the event and not addressing the content that contradicts their objectives (cf. Czachur 2011: 87). However, not only politically or socially crucial issues can become an object of discursiwe and shape the way knowledge is construed, often by the media. Based on two selected discourses which are culturally significant he article tries to identify both similarities and discrepancies in relation to passing on knowledgeabout two renown figures of culture by the media discourse actors. The analysis consisting in exploring discursive actions will lead to providing information about the level of knowledge of the actors in the two discourses, i.e. to determining what knowledge they have about a particular section of reality. The undertaken analysis does not employ typical methods of discourse analysis, but it proposes its own method, which is an extension of the previous investigation methods. It is based on the analysis of criticism, which in this case is understood as a complex linguistic act.